Hepatic Differentiated Embryo-Chondrocyte-expressed Gene 1 (Dec1) Inhibits Sterol Regulatory Element-binding Protein-1c (Srebp-1c) Expression and Alleviates Fatty Liver Phenotype - Shen, Lian (American Society for Biochemistry and Molecular Biology, 2014)
Hepatic steatosis, characterized by ectopic hepatic triglyceride accumulation, is considered as the early manifestation of non-alcoholic fatty liver diseases (NAFLD). Increased SREBP-1c level and activity contribute to excessive hepatic triglyceride accumulation in NAFLD patients; however, negative regulators of Srebp-1c are not well defined. In this study, we show that Dec1, a critical regulator of circadian rhythm, negatively regulates hepatic Srebp-1c expression. Hepatic Dec1 expression levels are markedly decreased in NAFLD mouse models. Restored Dec1 gene expression levels in NAFLD mouse livers decreased the expression of Srebp-1c and lipogenic genes, subsequently ameliorating the fatty liver phenotype. Conversely, knockdown of Dec1 expression by an adenovirus expressing Dec1-specific shRNA led to an increase in hepatic TG content in normal mouse livers. Correspondingly, expression levels of lipogenic genes, including Srebp-1c, Fas, and Acc, were increased in livers of mice with Dec1 knockdown. Moreover, a functional lipogenesis assay suggested that Dec1 overexpression repressed lipid synthesis in primary hepatocytes. Finally, a luciferase reporter gene assay indicates that DEC1 inhibits Srebp-1c gene transcription via the E-box mapped to the promoter region. Chromatin immunoprecipitation confirmed that DEC1 proteins bound to the identified E-box element. Our studies indicate that DEC1 is an important regulator of Srebp-1c expression and links circadian rhythm to hepatic lipogenesis. Activation of Dec1 can alleviate the nonalcoholic fatty liver phenotype.